Uso de atributos de código para classificar a dificuldade de questões de programação em juízes online - Lima, Marcos A. P. (2021)
In introductory programming classes, online judges are used as a tool for preparing assessments through a random draw of programming questions. For the random draw of questions to be balanced, questions should be classified according to their difficulty or ease. Thus, this work presents two approaches to classify programming questions by using attributes automatically extracted from solution codes for the questions. In total, 404 questions with implementation in Python were classified, which were used in evaluations of classes of introduction to programming taught between 2017 and 2019. Both approaches presented good results for dichotomous classification of programming questions.